2010
DOI: 10.1186/1752-1947-4-47
|View full text |Cite
|
Sign up to set email alerts
|

Patellar tendon ossification after partial patellectomy: a case report

Abstract: IntroductionPatellar tendon ossification is a rare pathology that may be seen as a complication after sleeve fractures of the tibial tuberosity, total patellectomy during arthroplasty, intramedullary nailing of tibial fractures, anterior cruciate ligament reconstruction with patellar tendon autograft and knee injury without fracture. However, its occurrence after partial patellectomy surgery has never been reported in the literature.Case presentationWe present the case of a 35-year-old Turkish man with a commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The scanned bar = 1000 μm for all. junction (Cakici et al, 2010;Kim et al, 2011). In the present study, we demonstrated that CMF promotes BT junction healing by enhancing the ossification after partial patellectomy in rabbit models.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The scanned bar = 1000 μm for all. junction (Cakici et al, 2010;Kim et al, 2011). In the present study, we demonstrated that CMF promotes BT junction healing by enhancing the ossification after partial patellectomy in rabbit models.…”
Section: Discussionsupporting
confidence: 62%
“…Caricin et al. reported that the restoration of the BT junction's mechanical strength was closely related with bone formation at the healing interface, and in some cases, the size and quality of new bone formation represented the degree of healing at the BT junction (Cakici et al., ; Kim et al., ). In the present study, we demonstrated that CMF promotes BT junction healing by enhancing the ossification after partial patellectomy in rabbit models.…”
Section: Discussionmentioning
confidence: 99%
“…Bone formation is a crucial stage in the process of BTJ healing . The size of the new bone corresponded to the degree of healing in the process of BTJ healing . From the radiographic results and histology, we can deduced that the size of new bone increased as the healing over time, more new bone and cartilage‐like tissue were formed in the LIPUS group than the control group at the same time point.…”
Section: Discussionmentioning
confidence: 94%
“…In literature the ossification of the patellar tendon has been reported mainly related to knee injuries [3,4] or as a consequence of total/partial patellectomy [5,6] and intramedullary nailing of the tibia [7-9]. A rare and interesting report was described by Chen et al, an extensive heterotopic ossification after patellar tendon repair in a 32-year-old African-American man with a rare trisomy 8 mosaicism.…”
Section: Discussionmentioning
confidence: 99%